The Effect of Sustainability Disclosure and Company Performance: Profit or Image? - Elfina Astrella Sambuaga (Jurnal Ilmiah Akuntansi, 2024)
This study examines the effect of company sustainability report disclosure on company performance, focusing on the environment, social, and governance (ESG) score and ESG Reporting score. The sample consists of non-financial companies listed on the Indonesia Stock Exchange during the 2015-2019 period, comprising 1,744 observations. The results reveal that sustainability report disclosure has a negative and significant effect on overall company performance. However, when examining profitability specifically, disclosing information on sustainability activities has a positive and partially significant effect. These findings support the theory of legitimacy, suggesting that companies engage in sustainability report disclosures to enhance their image. At the same time, the disclosures serve as a signal to investors and the market, aligning with stakeholder theory. This dual perspective underscores the complex role of sustainability reporting in corporate strategy and investor relations. By highlighting both the potential drawbacks and benefits of sustainability disclosures, this study provides valuable insights for companies, investors, and policymakers aiming to balance ethical practices with financial performance. Ultimately, the research contributes to the ongoing discourse on the impact of ESG factors on corporate success and the strategic importance of transparent sustainability reporting.